Accumulation of Human Capital and the Business Cycle - Fukao, Kyoji; Otaki, Masayuki (Journal of Political Economy, 1993)
Characteristics of business cycles are quite different across developed countries. Real wages and working hours a re less sensitive to exogenous shocks in the United States than in Brit ain and Japan. Using a model with a microeconomic foundation, this paper provides an economic explanation of these differences. The cost of on-the-job training plays a crucial role. Workers seldom quit their jobs when the sunk training cost is high. In such economies, varianc es in employment and output become small and shocks tend to be absorbed by working hours and real wages. Thus, these characteristics do not necessarily indicate that the economy is more efficient. Copyright 1993 by University of Chicago Press.